DESAIN PROTOTIPE MESIN RECOVERY DAN RECYCLE PORTABLE (JINJING) SEBAGAI PERALATAN PERBAIKAN PADA MESIN PENDINGIN DENGAN REFRIGERAN R22 - Billy Andang Baruna; Berkah Fajar TK. (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2015)
One of the environmental issues in this century that becomes the world’s concern is global warming and the destruction of the ozone layer. The cause of the damage or depletion of the ozone layer is by the emitted Bahan Perusak Ozon (BPO) from a variety of activities, either in using or producing goods that contain BPO. An example of BPO that is made by human is synthetic substances, the synthetic substances that have a quite high effect in polluting the environment is the refrigerant. Refrigerant R22 is a refrigerant that has Ozone Depletion Potential (ODP) value of 0.06 and Global Warming Potential (GWP) value of 1700. The value of the ODP and GWP is quite high and affects the environmental destruction. Therefore, it is designed a recovery and recycling machine of refrigerant R22. The purpose of this study is to design a recoveryrecycle machine (2R) and calculate and determine the components of the recovery and recycling prototype machine that are easy to be carried and to be used. The design process of 2R machine uses VDI 2221 and VDI 2225 guidelines. Identify the problem, make a list of needs (requirements list), make the working principle, build working structures, make morphology tables, make technical and economic evaluation, as well as make sketches of 2R machine, are the steps of 2R machine design process. 2R machine design is aimed at cooling machine Air-Conditioner vapor compression cycle and the type of refrigerant used is R22. The current existing recoveryrecycle machine is only for refrigerant R12 and R134. Therefore, 2R machine is designed for refrigerant R22 which has much smaller weight and size than 2R existing machine with a weight target of 20 kg and a volume of 0,036 m3. From the calculation result and tools selection, it is generated 2R machine with specifications of 20 kg of weight, length of 40 cm, width of 30 cm, height of 30 cm, hermetic compressor of 0.25 HP (186.5 Watts) 1 piece, condenser of 2050 btu/hr 1 piece, a piece of 1 ½ inch oil separator brand EMERSON, ¼ inch copper pipe, 2 pieces of filter dryer brand EMERSON and 2 pieces of pressure gauge. With the use of recycled R22 that was wasted to the atmosphere and potentially damage the ozone layer, now it can be reused. This supports the world's commitment to reduce and stop the use of bahan perusak ozon (BPO) for both household and industrial needs in the long run